The Existence of Amicus Curiae in Constitutional Court Decisions: A Participation Theory Perspective - Annisa Mayang Tyaningrum; Muchamad Ali Safa’at; Ngesti Dwi Prasetyo (International Journal of Islamic Education, Research and Multiculturalism)
This study explores the role of amicus curiae in Constitutional Court decisions through participation theory, highlighting the importance of public involvement in legal decision-making. As a form of non-litigation participation, amicus curiae provides legal insights and diverse perspectives, aiding judges in balancing legal certainty, justice, and utility, particularly in cases of public significance. The research examines how amicus curiae aligns with participation theory and analyzes its influence on the Indonesian Constitutional Court. Using normative legal research, the findings reveal that amicus curiae enhances decision quality, transparency, and accountability while reflecting active public engagement. This mechanism underscores the Court's commitment to a democratic and inclusive legal system, making the role of amicus curiae both relevant and strategic in upholding constitutional justice.